Analysis of chaos in the combustion process of premixed natural gas engine. (5th July 2017) - Ding, Shun-Liang; Song, En-Zhe; Yang, Li-Ping; Litak, Grzegorz; Wang, Yu-Yuan; Yao, Chong; Ma, Xiu-Zhen
Highlights: The 0–1 test is applied to study the chaotic characteristics of combustion process. The normalized time series and all the c   ∈  (0, π ) values are used for the 0–1 test. The injection timing is used as the impact factor. The reliability of 0–1 test method is validated by phase space reconstruction. The chaotic behavior is stronger under 45–60°CA injection timing conditions. Abstract: In this paper, the dynamical characteristics of a combustion process in the premixed natural gas engine are studied with the phase space reconstruction method and the 0–1 test method. To express the influence of the system parameters the experiments are carried out under different injection timing conditions. The results express that by reconstructing the phase space, the patterns of combustion process can be clearly investigated. The attractors of in-cylinder pressure, IMEP, Q and θ 50 time series exhibit more serious variations when the injection timing is 45–60°CA. The normalized time series is proposed to be used in the coordinates of the 0–1 test. In the results we obtained the characteristic values of the control parameter, K, is close to 0 for a motored engine and 1 for all the cases with different injection timings. Moreover, with increasing of the injection timing, the K value firstly increase and then decrease. The results demonstrate that the combustion process of a premixed natural gas engine under different injection timing conditions is considered to be chaotic. Furthermore, the chaotic behavior is stronger under 45–60°CA injection timing conditions. This coincides with the phase space reconstruction results.